Calcitonin Gene-Related Peptide in Tension-Type Headache - M. Ashina (The Scientific World Journal)
In the last 10 years there has been increasing interest in the role of calcitonin gene-related peptide (CGRP) in primary headaches. Tension-type headache is one of the most common and important types of primary headaches, and ongoing nociception from myofascial tissues may play an important role in the pathophysiology of this disorder. CGRP sensory fibers are preferentially located in the walls of arteries, and nerve fibers containing CGRP accompany small blood vessels in human cranial muscles. It is well established that nociception may lead to release of CGRP from sensory nerve endings and from central terminals of sensory afferents into the spinal cord. It has also been shown that density of CGRP fibers around arteries is increased in persistently inflamed muscle. These findings indicate that ongoing activity in sensory neurons in the cranial muscles may be reflected in changes of plasma levels of neuropeptides in patients with chronic tension-type headache. To explore the possible role of CGRP in tension-type headache, plasma levels of CGRP were measured in patients with chronic tension-type headache. This study showed that plasma levels of CGRP are normal in patients and unrelated to headache state. However, the findings of normal plasma levels of CGRP do not exclude the possibility that abnormalities of this neuropeptide at the neuronal or peripheral (pericranial muscles) levels play a role in the pathophysiology of tension-type headache. Investigation of CGRP in other compartments with new sensitive methods of analysis is necessary to clarify its role in tension-type headache.